Analyzing the Pattern of L1 Sounds on L2 Sounds Produced by Javanese Students of STKIP PGRI Jombang - Daning Hentasmaka (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2015)
The studyconcerns on an analysis on the tendency of first language (L1) sound patterning on second language (L2) sounds done by Javanese students.Focusing on the consonant sounds, the data were collected by recording students’ pronunciationof English words during the pronunciation test. The data then analysed through three activities: data reduction, data display, and conclusion drawing/ verification. Theresult showedthatthe patterning of L1 sounds happened on L2 sounds especially on eleven consonant sounds: the fricatives [v, θ, ð, ʃ, ʒ], the voiceless stops [p, t, k], and the voiced stops [b, d, g].Thosepatterning case emergedmostlyduetothe difference in the existence of consonant sounds and rules of consonant distribution. Besides, one of the cases was caused by the difference in consonant clusters between L1 and L2.